Valoración del alcance de la teoría de las representaciones semióticas de Duval para caracterizar el pensamiento matemático mostrado por estudiantes que participan en los exámenes de olimpiadas colombianas de matemáticas - Guerrero Morales, Lexander (Universidad Antonio Nariño, 2023)
Raymond Duval's theory of semiotic representations constitutes a semiotic approach to Mathematics Education that proposes explaining complex phenomena such as the cognitive functioning of Mathematical Thinking and comprehension in mathematics, starting only by taking into account such representations and their transformations.